Developing a model for the Life Cycle Assessment of the Parmigiano- Reggiano cheese - Fornasari, L. (Progress in Nutrition, 2013)
The actors involved within the Parmigiano-Reggiano food chain are growing their interest about environmental issues related to this important PDO product. This study aimed to develop a model for applying Life Cycle Assessment (LCA) methodology to this product system, and through this model, to identify major impacts and hot spots. Applying this model to a specific organic dairy farm, and the related product system, this study showed that major environmental impacts for all impact categories considered are related to the agricultural phase, mainly land occupation for fodder production, and greenhouse gases (methane and nitrous oxide) from enteric fermentation and manure management. Infrastructure, mainly buildings, showed to have great importance in some impact categories.